Can we afford to offer pre-exposure prophylaxis to MSM in Catalonia? Cost-effectiveness analysis and budget impact assessment. Issue 6 (3rd June 2018) - Reyes-Urueña, J.; Campbell, C.; Diez, E.; Ortún, V.; Casabona, J.
ABSTRACT: Pre-exposure prophylaxis (PrEP) effectiveness has been well established. This study aims to assess the cost-effectiveness of providing PrEP, estimate the number of eligible MSM, and its budget impact in Catalonia. Cost-effectiveness analysis compared costs of on daily basis and "on demand" PrEP to prevent one infection with lifetime costs of one HIV infection. We estimated the total cost of providing PrEP by estimating number of eligible MSM, and included in the budget impact assessment antiretroviral and laboratory costs. Costs were lower for the on-demand PrEP group by €64015.1 and the incremental benefit was nearly 15 life-years and 17 quality-adjusted life-years gained. The incremental cost-effectiveness ratio (ICER) was cost-effective at €6281.62 when undiscounted PrEP was given daily. On-demand PrEP can be considered cost-saving in 20 years if the price is reduced by 90%. The number of eligible MSM in Catalonia ranges from 5, 989 to 10, 972. At current antiretroviral costs, the annual cost would range between €25.3–46.7 million/year (on demand PrEP), and €42.9–78.7 million/year (daily basis PrEP). PrEP is most cost-effective if targeted towards groups with high incidence rates of over 3%/year. Beneficial ICER depends on reducing the current price of Truvada® and ensuring that effectiveness is maintained at high levels.